Failure analysis of hybrid fibre reinforced plastics for bolted joint under thermal effect / D. Sivakumar...[et al.] - D., Sivakumar; L.F., Ng,; Selamat, M. Z. (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2017)
Composite material is gaining a large attention in these few years due to its high strength to weight ratio. The cost of composite is also relatively lower than conventional metallic alloy. Several previous studies had shown introducing of synthetic fibre in the natural fibre-based composite polymer can enhance the mechanical strength of the composite structure. This research paper studies the effect of temperature and preload moment on the bearing strength of woven kenaf-glass fibre reinforced polypropylene hybrid composite. The kenaf fibre and E-glass fibre are in the form of plain weave fabric. Composite specimens were manufactured through hot press moulding compression method at 180ºC. In bolted joint test, specimens were exposed to a temperature of 25ºC (room temperature), 40ºC, 50ºC, and 60ºC and tightened with 0Nm, 5.2Nm and 7.5Nm preload moment. Bearing response under different conditions was tested according to ASTM D5961 standard procedure and failure modes were observed. The results revealed that increase in the ambient temperature reduced the bolted joint strength whereas the increase in preload moment improved the joint strength.